Situation Report: Romania, 22 April 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu to Paris in June Relations with Middle East Countries Diplomatic Activities Turkish-Romanian Communique Lenin Anniversary Congress of Consumer Co-Operatives Decree on Taxes and Duties Foreign Trade in the First Quarter of 1970 Coverage of Apollo 13 Mission